A multi-methodological approach to studying time-pressure in written translation: Manipulation and measurement - Weng, Yu; Zheng, Binghan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The effect of time pressure on task performance of written translation has been researched since the 1990s. However, little attention has been paid to the methodological issues of manipulating and measuring time pressure in these empirical studies. To bridge this gap, we propose a methodological framework involving diverse approaches to time-pressure manipulation and measurement. Specifically, in addition to objectively constraining the time frame for a task, we present three subjective time-pressure manipulation strategies: giving pre-task instructions about time, increasing participants’ intrinsic motivation for the task, and visualizing the elapse of time. Meanwhile, a range of feasible methods of time-pressure measurement is structured from the physiological, psychological and behavioural perspectives. This includes physiological measures such as galvanic skin response, heart rate, blood pressure, pupil dilation and salivary cortisol test, psychological measures such as psychometric instruments and retrospective questionnaires, and behavioural measures such as eye movements and keystroke activities. Based on a thorough survey of existing studies and the merits borrowed from neighbouring disciplines, this article aims to strengthen and enrich the methodology of time-pressure studies and benefit future translation research on relevant topics.